THE DEVELOPMENT OF MARKET ORIENTED CROP PRODUCTION AS A FACTOR IN REDUCING RURAL POVERTY IN SERBIA - Simo Stevanović; Milutin T. Đorović (Ekonomika Poljoprivrede (1979), 2011)
This paper analyses the development of market orieneted production of major crop products by districts in 2009, in order to reduce rural poverty in the Republic of Serbia.